Coronal and sagittal spinal alignment in lumbar disc herniation with scoliosis and trunk shift - Wu, Weifei; Chen, Ying; Yu, Ling; Li, Fei; Guo, Weichun (Journal of orthopaedic surgery and research, 2019)
To investigate the incidence of scoliosis and trunk shift in patients with LDH (lumbar disc herniation) and analyze the differences in spinopelvic alignment among patients with or without trunk shift and non-symptom controls. All included subjects had standard upright antero-posterior and lateral radiographs of the whole spine taken. Evidence of disc herniation was confirmed by computed tomography or magnetic resonance imaging. The parameters measured included trunk shift and Cobb angle, TK (thoracic kyphosis), TLK (thoraco-lumbar junction kyphosis), LL (lumbar lordosis), PI (pelvic incidence), SS (sacral slope), PT (pelvic tilt) and SVA (sagittal vertical axis). Sixty-eight patients with LDH and 61 controls were included. There were significantly more male patients with trunk shift than the patients without trunk shift. Forty-two patients had curve magnitudes ranging from 5 to 38°. The trunk shift ranged from 0.5 to 7.3 cm. A total of 54.76% of patients had a disc herniation on the concave side of the main curve. Fifty percent of patients showed a trunk shift towards the opposite side of disc herniation. There were significant differences in spinopelvic parameters among groups. Significant correlations were also observed between several spinopelvic parameters in the three groups. However, the degrees of correlations among the spinopelvic parameters differed among the three groups. Spinal sagittal morphology in LDH patients with trunk shift exhibits a more anterior shift of the C7 plumb line, less LL, and a more horizontal sacrum. Correlation analysis indicated a disharmonious spinopelvic interaction and a change in the compensatory model in patients with LDH.